2019
DOI: 10.3390/insects10070211
|View full text |Cite
|
Sign up to set email alerts
|

Diachasmimorpha longicaudata Parasitism Response to Medfly Host Fruit and Fruit Infestation Age

Abstract: The parasitoid Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) is increasingly being used in integrated pest management (IPM) programs as a biological control agent in order to suppress tephritid fruit flies of economic importance. Innate and acquired behavioral responses—such as pest host fruit preference—of parasitoids can modulate their efficiency in the field and should be taken into consideration prior to parasitoid species’ selection for mass-rearing. We have assessed the influence of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…Harbi and colleagues demonstrated a multistep assay (e.g., olfactory, laboratory, and semi-field trials) and reported the preference of medfly-infected fruits, including apple, orange, peach, and clementine mandarins [18]. This experiment supports that different olfactory genes are expressed in response to different fruit scents.…”
Section: Introductionmentioning
confidence: 89%
“…Harbi and colleagues demonstrated a multistep assay (e.g., olfactory, laboratory, and semi-field trials) and reported the preference of medfly-infected fruits, including apple, orange, peach, and clementine mandarins [18]. This experiment supports that different olfactory genes are expressed in response to different fruit scents.…”
Section: Introductionmentioning
confidence: 89%
“…Aganaspis pelleranoi has been reported to be more attracted to volatiles of guavas infested with frugivorous larvae [ 47 ]. For its part, the females of D. longicaudata , which is one of the most widely employed species against tephritids [ 13 ], have also shown a significant preference for fruits infested with larvae of the medfly and/or other fruit flies [ 36 , 48 ]. In this regard, larvae in rotting fruits have long been believed to release or induce the formation of volatiles that are attractive to parasitoids when compared with uninfested ripe fruit [ 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was connected to an air pump producing a unidirectional airflow of 150 mL/min from the arms to the base (wind speed of 0.005 m/s). Airflow was established based on previous experiments with similar-sized insects [ 30 , 34 , 35 , 36 ]. The air pump was connected to two 5-L crystal jars containing the odor sources to be evaluated (in this case, test fruits).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct and indirect damage is caused by Anastrepha and Ceratitis, thus the biological control of fruit flies has great economic and environmental importance, providing increased research aimed at the use of the organisms Diachasmimorpha Research, Society and Development, v. 10, n. 1, e22510111245, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i1.11245 longicaudata, Doryctobracon areolatus, Beauveria bassiana, Wolbachia, and Bacillus thuringiensis, who are responsible for controlling this pest (Harbi et al, 2019).…”
Section: Control Agents Analyzed By Categoriesmentioning
confidence: 99%